A history of the assessment of sex offenders : 1830-2020 - Laws, D. Richard (Bingley, U.K. : Emerald Publishing Limited, 2020)
Most forensic psychologists, psychiatrists and social workers involved in the assessment of sex offenders today have a good grasp of where the field stands. Many of their colleagues do not have an appreciation of why we are where we are. This book is an attempt to bridge that gap, to provide some historical background of sex offender assessment from 1830 to the present. Topics covered in this book include early efforts to identify and describe criminal populations statistically; the introduction of phrenology as a description of brain function; the efforts of criminal anthropologists to develop criminal taxonomies; the technology of anthropometry to identify individuals by measurement of bodily structure; and the introduction of fingerprinting which replaced anthropometry and remains largely unchanged to the present day. The guiding principle of the book is to help the reader understand that all of this represents a continuous thread of development and, disparate as they might seem, all of them are connected. This book is essential reading for undergraduates in psychology and sociology, as well as professionals in training and early stages of practice.
Part I: Introduction -- Chapter 1: Contemporary psychological assessment: two approaches -- Part II: Assessment of criminal and sex offenders: 19th and 20th centuries -- Chapter 2: Criminal statistics and the identification of populations -- Chapter 3: Offender classification and registration -- Chapter 4: Phrenology: pseudoscience of the mind or precursor science? -- Chapter 5: Criminal anthropology: Lombroso's search for criminal man -- Chapter 6: Anthropometry: Bertillon's measurement of criminal man -- Chapter 7: Fingerprinting: a document complete in itself -- Part III: Assessment of sex offenders: 20th and 21st centuries -- Chapter 8: Penile plethysmography: the search for the gold standard -- Chapter 9: Viewing time: an alternative to PPG -- Chapter 10: Attention-based measures: supplementary procedures -- Chapter 11: Polygraphy: the bogus pipeline to the soul -- Part IV: Assessment of sex offenders: possible futures -- Chapter 12: Virtual reality assessment: being there -- Part V: Conclusions -- Chapter 13: What we learned in 190 years: 12 takeaways -- Index.
Includes index.
Print version record.
Keywords: Sex offenders -- History; Criminal anthropology; Sex offenders -- Psychology; Social Science -- Criminology; Crime & criminology